The promise of cinema : German film theory, 1907--1933 - Kaes, Anton; Baer, Nicholas, 1985-; Cowan, Michael J., 1971- (Weimar and now., 2016)
Rich in implications for our present era of media change, The Promise of Cinema offers a compelling new vision of film theory. The volume conceives of "theory" not as a fixed body of canonical texts, but as a dynamic set of reflections on the very idea of cinema and the possibilities once associated with it. Unearthing more than 275 early-twentieth-century German texts, this ground-breaking documentation leads readers into a world that was striving to assimilate modernity's most powerful new medium. We encounter lesser-known essays by Béla Balázs, Walter Benjamin, and Siegfried Kracauer alongs.